Makna Sajak-sajak `tembang' Karya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This research entitled "The Meaning of D. Zawawi Imron's Song Poems: A Semiotic Study" is intended to interpret seven song poems taken from his eleven poem collections. The poems discussed are (1) 'Tembang Kasmaran', (2) 'Tembang Alam', (3) 'Tembang', (4) 'Tembang I', (5) 'Tembang Nelayan', (6) 'Tembang Rohani', and (7) 'Tembang Dahaga'. Riffaterre semiotic theory is applied to analyze the seven chosen poems. This is a qualitative research which applied semiotic theory and method. By using this method, the writer analyzes the poems through two reading steps, namely heuristic and hermeneutic reading. Then they are identified their matrix, model, variation and intertextual relationship. The result of the study shows that heuristically and herme-neutically Imron's poems contain figure of speech arousing indirect expression. The meanings of D. Zawawi Imron's song poems are: (1) inflaming love and dreaming of ha py life, (2) hamonious relation between man and nature, (3) a lonely heart, 4) proud of homeland, (5) zest for fishermen, (6) remain ding human spirit of its promises, and (7) a thirsty human soul. Of three poems are hypograms of Queanic verses: (1) the poem 'Tembang Alam' is ispired by chapter 36, Surah Yasin, verses 38 and 40